1996
DOI: 10.1002/(sici)1097-4628(19960912)61:11<1887::aid-app4>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Rheological behavior of degraded polypropylene melts: From MWD to dynamic moduli

Abstract: SYNOPSISThe linear viscoelastic behavior of polydisperse polypropylenes in the melt is predicted using the molecular weight distribution (MWD) as determined from gel permeation chromatography, on the basis of simplified molecular dynamics: single exponential form of the relaxation modulus of narrow fractions, double reptation, tube renewal, and constraint release. Owing to a few approximations, the calculation only requires a few parameters, namely the scaling law for the zero shear viscosity of narrow fractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
2

Year Published

2000
2000
2009
2009

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 0 publications
1
28
2
Order By: Relevance
“…As the viscosity of the polymer solution depends basically on the MWD of the polymer produced, as polymer concentrations do not vary very much, it may be related to the melt flow index of the polymer as 17 :…”
Section: Physical Propertiesmentioning
confidence: 99%
“…As the viscosity of the polymer solution depends basically on the MWD of the polymer produced, as polymer concentrations do not vary very much, it may be related to the melt flow index of the polymer as 17 :…”
Section: Physical Propertiesmentioning
confidence: 99%
“…where k E is the constant of proportionality and generally lies between 3.3 and 3.7, except for extremely broad blends, for which higher values are observed [13][14][15][16]. is often taken as 3.4, since this is the value usually obtained for most linear polymers investigated.…”
mentioning
confidence: 99%
“…Because of that, these products are referred to as Controlled-Rheology Polypropylenes (CRPP). The importance of this can be shown by referring to Several researchers have studied MWD of CRPP (Tzoganakis (1988, Malz (1995), Bonilla -Rios et al (1995), Carrot et al (1996), BonillaRios et al (1998), Asteasuain et al (2003)). In general, it has been concluded that CRPP resins have lower molecular weight, narrower MWD and reduced viscosity.…”
Section: Degradation Of Polypropylene (Pp)mentioning
confidence: 99%